Pengaruh Kompetensi Dan Motivasi Auditor Terhadap Kualitas Audit Pada Kantor Inspektorat Kabupaten Rokan Hulu - Sri Yuna Wati (Jurnal Ilmiah Cano Ekonomos, 2018)
This research aims to examine the influence of competence and motivation on the audit quality of the inspectorate of the Rokan Hulu district, the general problem found in this research is the audit findings detected by the inspectorate apparatus as the internal government auditor, but found by the external auditor, ). Data were collected from questionnaires distributed from respondents. The independent variables are competence (X1) and motivation (X2), while the dependent variable is audit quality (Y). The data were analyzed by using multiple linear regression, and hypothesis test that is F test and t test. The result of the research in this research is that simultaneously by using F test, the competence and motivation of the auditor have an effect on the quality of audit. While partially using t test, auditor competence variables affect the quality of audits while auditor motivation does not affect the auditor's motivation.